Philosopher King VS. Loafer King: A Critical Appraisal of Pakistan in Post 2013 General Elections to Date - Dr. Rana Eijaz Ahmad (Journal of Political Studies, 2020)
This paper is going to explain how a competent and talented leader with charismatic potentials ensures the socio-political and economic development of a country. It is also mentioned that how classical philosopher-king had been different from the contemporary loafer king. Pakistan has been a victim of political instability owing to the personal jealousies of political demagogues and the dejure political elite. There has been a conventional practice of apathy regarding holding elections at the party level within the so-called political parties of Pakistan. Since the definition of political science calls for a political strive of a group of people may be having a like-minded goal known as a political party. There are only interest groups in Pakistan rather than any political party. Such interest groups hardly create Philosopher Kings but of course Loafer Kings. However, the electoral process is an essential procedure where citizens of any country are allowed to select their leaders to rule the country according to the law of the land. The main objective of this paper is to highlight the difference between the phenomenon of Plato’s Philosopher King (PK) and the contemporary world’s Loafer King (LK) that signifies the present-day leadership of the world as well as in Pakistan. Therefore, major changes took place in Pakistan in the post-2013 General Elections. It sheds light on the complexities between the numerous political parties how they are playing cards in Pakistan to become more successful than the other. The institutions are at the helm of sorry affairs owing to the inefficiency and tunnel vision of the so-called leadership in Pakistan.